Enhancing Workers’ Protection in Jordan - Rother, Friederike (World Bank, Washington, DC, 2022)
This paper exploits a rich database to provide comprehensive profiling of informality in Jordan, including who informal workers are, their characteristics, and where they work, as well as providing policy recommendations to address informality. The structural framework developed through the comprehensive profiling is followed by an analysis of why workers are informal, using inferential multivariate analysis. Statistical techniques (that is, cluster analysis) are used to group workers by similar characteristics (including education, gender, income, and form of employment) to allow policy makers to pinpoint specific policy tools that can target each group. The paper offers long term policy solutions to address informality, including fostering competition to boost productivity and providing a level playing field. It also proposes short, and medium-term policy options to protect workers against shocks until more productive jobs are created, for instance through the provision of short-term benefits through defined contribution schemes. Heterogeneity is addressed by tailoring policy instruments to clusters of workers.